2016
DOI: 10.1017/s0266467416000067
|View full text |Cite
|
Sign up to set email alerts
|

Gene flow and fine-scale spatial genetic structure inCabralea canjerana(Meliaceae), a common tree species from the Brazilian Atlantic forest

Abstract: Abstract:The Atlantic forest is the biome most severely affected by deforestation in Brazil. Cabralea canjerana spp. canjerana is a dioecious tree species with widespread distribution in the Neotropical region. This species is considered a model to ascertain population ecology parameters for endangered plant species from the Atlantic forest. Fine-scale spatial genetic structure and pollen-mediated gene flow are crucial information in landscape genetics and evolutionary ecology. A total of 192 adults and 121 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The significant fragmentation of the savanna biome may decrease or even interrupt many reproductive and demographic processes of tree species, such as pollen and seed flow and colonization (Collevatti et al 2013, Baldauf et al 2014, Ibanes et al 2016. Studies have shown that forest fragmentation can lead to decreased population size (genetic bottleneck effect), spatially isolated trees and populations, reductions in gene flow, genetic diversity, and effective population size, and increases in selfing rates, spatial genetic structure, and genetic divergence among populations of remnant tree species (Bittencourt & Sebbenn 2007, Melo & Franceschinelli 2016). All of these processes increase the probability of population extinction.…”
Section: Introductionmentioning
confidence: 99%
“…The significant fragmentation of the savanna biome may decrease or even interrupt many reproductive and demographic processes of tree species, such as pollen and seed flow and colonization (Collevatti et al 2013, Baldauf et al 2014, Ibanes et al 2016. Studies have shown that forest fragmentation can lead to decreased population size (genetic bottleneck effect), spatially isolated trees and populations, reductions in gene flow, genetic diversity, and effective population size, and increases in selfing rates, spatial genetic structure, and genetic divergence among populations of remnant tree species (Bittencourt & Sebbenn 2007, Melo & Franceschinelli 2016). All of these processes increase the probability of population extinction.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the pollen dispersal distance and geographic arrangement of the population fragments, the fragment groups 1, 2, 3, and 4 were exchange genes with each other. This exchange was also observed between fragments 5 and 6, but not in the groups that were over 1,040 m apart (MELO & FRANCESCHINELLI, 2016). Thus, only the spatial model of isolation by distance with migration rate of 0.1 could explain the pattern of gene flow between the eight C. canjerana fragments studied ( Table 2).…”
Section: Model Selectionmentioning
confidence: 80%
“…The EASYPOP Version 2.0.1 software (BALLOUX, 2001) was used to simulate different models and flow rates, which were selected based on how well they could explain the genetic structure of eight C. canjerana fragments obtained by six microsatellite markers from MELO (2012), MELO et al 2014and MELO & FRANCESCHINELLI (2016). In these population fragments studied were sampled: (#1) 27, (#2) 33, (#3) 31, (#4) 33, (#5) 17, (#6) 11, (#7) 39, and (#8) 30 individuals.…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A third study conducted with 100 S. macrophylla trees sampled in Costa Rica forests and using five microsatellite loci obtained average H O and H E of 0.508 and 0.518 (Céspedes et al, 2003). By sampling 192 Cabralea canjerana (Meliaceae) trees in seven fragments of the Atlantic Forest in the state of Minas Gerais, Melo and Franceschinelli (2016) observed H O and H E of 0.70 and 0.73, using six microsatellite loci.…”
Section: Discussionmentioning
confidence: 93%